Monetary policy and its impact on achieving economic stability in Yemen for the period (1990-2004) - Al-Sqqaf, Yahya Ali Yahya (Journal of Economic, Administrative and Legal Sciences, 2023)
The research deals with monetary policy and the effectiveness of its tools in achieving economic stability in Yemen in the period after the establishment of the blessed Yemeni unity from the year 1990-2004 AD, in an analytical way of researching monetary policy tools and their impact on achieving economic stability. Through the process of attracting savings and financing investment projects, where monetary policy contributes to the process of economic development by measuring some data of the Central Bank of Yemen during the study period, which the researcher concluded in the presence of relative stability in the exchange rate and the growth rate of domestic liquidity and an increase in the volume of loans and the volume of reserves. The foreign affairs of the banking system and the impact of all this in directing savings to the money supply and controlling it to the extent commensurate with growth rates and thus achieving economic stability. It can be said that monetary policy is the policy of the Central Bank to provide the necessary funding for the development process. The mission is to highlight the role of monetary policy in achieving economic stability and the most important recommendations are the need to activate indirect monetary policy tools, especially the open market tool, and work to activate the financial market to ensure the mobilization of financial resources.